Teori, Tema dan Perkembangan Penulisan Sejarah Ekonomi Islam. Suatu Tinjauan Awal - Maryani, Lesi (Al-aqidah | Jurnal Studi Islam, 2018)
History as the major field of research that related with the political event, such as: throne seizure of throne, expansion, warfare and heroism for the sake of the group. For historical critics a variety of new worldviews dissect the past. One alternative approaches of the economy as a primary need. The civilization is not only measured by the splendor of the building and the territorial breadth, but also the prosperity of the economy. This is interesting to note, the fruit of past events, is felt now. The discourse of Islamic economic history is part of general economic history, needs to be developed. This paper focuses on the future writing of Islamic economic history and themes for historians and academics.